What Do You Mean, No? Toddlers' Comprehension of Logical "No" and "Not". Issue 4 (2nd October 2017) - Feiman, Roman; Mody, Shilpa; Sanborn, Sophia; Carey, Susan
ABSTRACT: For adults, "no" and "not" change the truth-value of sentences they compose with. To investigate children's emerging understanding of these words, an experimenter hid a ball in a bucket or a truck, then gave an affirmative or negative clue (Experiment 1: "It's not in the bucket"; Experiment 2: "Is it in the bucket?"; "No, it's not"). Replicating Austin, Theakston, Lieven, & Tomasello (2014), children only understood logical "no" and "not" after age two, long after they say "no" but around the time they say "not" and use both words to deny statements. To investigate whether this simply reflects improving inhibitory control, in Experiment 3 we showed children that one container did or did not hold the ball. Twenty-month-olds now succeeded. We discuss two possible factors limiting learning both "no" and "not"—a purely linguistic difficulty learning the labels, and the possibility that negation is unavailable to thought before age two.